PHOSPHORIC ACID FRACTIONATION FACTORS FOR SMITHSONITE AND CERUSSITE BETWEEN 25 AND 72°C - Gilg H.A.; Struck U.; Vennemann T.; Boni M. (My University, 2003)
The intramolecular kinetic oxygen isotope fractionation between CO2 and CO32- during reaction of phosphoric acid with natural smithsonite (ZnCO3) and cerussite (PbCO3) has been determined between 25 and 72°C. While cerussite decomposes in phosphoric acid within a few hours at 25°C, smithsonite reacts very slowly with the acid at 25°C providing yields of CO2 < 25% after 2 weeks. The low yields result in a low precision for oxygen isotope measurements of the acid-liberated CO2 (+/-1.65%%, 1σ, n = 9). The yield and reproducibility of oxygen isotope values of the acid-liberated CO2 from smithsonite can be improved, the latter to ~+/-0.15%%, by increasing the reaction temperature to 50°C for 12 h or to 72°C for 1 h. Our new phosphoric acid fractionation factor for natural cerussite at 25°C deviates significantly from a previously published value on synthetic material. The temperature dependence of the oxygen isotope factionation factor, α between acid-liberated CO2 and carbonate at 25 to 72°C is given by the following equations 1000lnαph°sCO2-cerussite = 5.13 (+/-0.15) + 4.79 (+/-0.15) x 105/T2 1000lnαph°sCO2-smithsonite = 3.96 (+/-0.21) + 6.69 (+/-0.22) x 105/T2 with temperature T in kelvin. A comparison with published equations of the form 1000lnαph°sCO2-carbonate = A + B x 105/T2 for other divalent metal carbonates shows that the factors B of slowly-reacting carbonates from the rhombohedral calcite group (magnesite, siderite, smithsonite and rhodochrosite) are very similar (6.7 +/- 0.2) and distinct from those of fast-reacting minerals witherite, cerussite, and strontianite of the orthorhombic aragonite group (4.5 +/- 0.3) and calcite (5.6 +/- 0.1). These differences indicate a crystallographic control on the temperature dependence of the kinetic oxygen isotope fractionation between phosphoric acid liberated CO2 and carbonate.